Knowledge domain and emerging trends in diabetic cardiomyopathy: A scientometric review based on CiteSpace analysis - Tao, Shiyi; Yang, Deshuang; Zhang, Lanxin; Yu, Lintong; Wang, Zihan; Li, Lingling; Zhang, Jin; Yao, Ruiqi; Huang, Li; Shao, Mingjing (Frontiers in Cardiovascular Medicine, 2022)
Objective To review the literature related to diabetic cardiomyopathy (DCM), and investigate research hotspots and development trends of this field in the relevant studies based on CiteSpace software of text mining and visualization in scientific literature. Methods The relevant literature from the last 20 years was retrieved from the Web of Science (WoS) Core Collection database. After manual selection, each document record includes title, authors, year, organization, abstract, keywords, citation, descriptors, and identifiers. We imported the downloaded data into CiteSpace V (version 5.8.R2) to draw the knowledge map and conduct cooperative network analysis, cluster analysis, burst keyword analysis, and co-citation analysis. Results After manual screening, there were 3,547 relevant pieces of literature published in the last 18 years (from 2004 to 2021), including 2,935 articles and reviews, which contained 15,533 references, and the number was increasing year by year. The publications of DCM were dedicated by 778 authors of 512 institutions in 116 countries. The People's Republic of China dominated this field (1,117), followed by the USA (768) and Canada (176). In general, most articles were published with a focus on “oxidative stress,” “heart failure,” “diabetic cardiomyopathy,” “dysfunction,” “cardiomyopathy,” “expression,” “heart,” “mechanism,” and “insulin resistance.” Then, 10 main clusters were generated with a modularity Q of 0.6442 and a weighted mean silhouette of 0.8325 by the log-likelihood ratio (LLR) algorithm, including #0 heart failure, #1 perfused heart, #2 metabolic disease, #3 protective effect, #4 diabetic patient, #5 cardiac fibrosis, #6 vascular complication, #7 mitochondrial dynamics, #8 sarcoplasmic reticulum, and #9 zinc supplementation. The top five references with the strongest citation bursts include “Boudina and Abel”, “Jia et al.”, “Fang et al.”, “Poornima et al.”, and “Aneja et al.”. Conclusion The global field of DCM has expanded in the last 20 years. The People's Republic of China contributes the most. However, there is little cooperation among authors and institutions. Overall, this bibliometric study identified the hotspots in DCM research, including “stress state,” “energy metabolism,” “autophagy,” “apoptosis,” “inflammation,” “fibrosis,” “PPAR,” etc. Thus, further research focuses on these topics that may be more helpful to identify, prevent DCM and improve prophylaxis strategies to bring benefit to patients in the near future.